Parametrik ve semiparametrik logit modelleri ile hanehalkı yoksulluğunun analizi - Dayıoğlu, Tuğba (My University, 2011)
Semiparametrik Logit Model, parametrik and semiparametrik logit modelleri performansının karşılaştırılması , hanehalkı yoksulluğu ÖZET Bu tezin amacı hanehalkı yoksulluğunu ve hanehalkı yaşam standartını etkileyen faktörlerle , Türkiye hanehalkı yoksulluğunun olasılığını parametrik logit ve semiparametrik logit modellerini S-PLUS programıyla tahmin etmektir ve performanlarını karşılaştırmaktır. Bu çalışmada TÜİK (Türk İstatistik Enstitüsü) Hanehalkı Bütçe Anket verileri kullanılmıştır. 2002-2005,2008 yılları için hanehalkı yoksulluğu parametrik ve semiparametrik logit modelleri uygulanarak analiz edilmiştir. Parametrik model yaklaşımları ihlal edildiğinde semiparametrik yaklaşım hem parametrik hem de nonparametrik yaklaşımın birleştiren bir yöntem olarak ele alınmaktadır. Bu tezde eşdeğer fert başına tüketim harcaması ve buna bağlı faktörler ele alınarak yoksulluğun boyutu ele alınarak görüntülenmesi denenmiştir. Uygulamada Hanehalkı Bütçe anketi verileri üç yıl arayla ele alınarak yatay kesit veri kullanılmıştır. Hanehalkı yoksulluğunun olasılığı parametrik logit modelleri ,nonparametrik logit modeli ve semiparametrik logit modelleri ile karşılatırılmıştır. Modellerin performansı belirli performans kriterlerine dayanarak hem de grafiklere dayanarak incelenmiştir. Key words :Semiparametric Logit Models, ,Comparing the parametric and semiparametric logit for goodness of fit ,deviance and sum of squared residuals

ANALYSİNG THE HAUSEHOLD POVERTY WİTH PARAMETRİC AND SEMİPARAMETRİC LOGİT MODELS Objectives of this thesis are to determine the factors which could affect poverty status and living standard of household and to illustrate the probabilities of poverty on household bases in Turkey and testing the parametric logit models and against their semiparametric al- ternatives in S-PLUS package. In this thesis we use the data of Turkish Hausehold Budget Survey prepared by Türkish Statistical Institute (TURKSTAT) for the years 2002,2005,2008 and analyze the factor affecting the poverty of Turkish Hauseholds by applying Semiparametric Logit Models .The semiparametric method that combines the best features of the parametric and the nonparametric approaches are introduced when the parametric model assumptions are violated. In the thesis, significant factors which determine the living standard according to the household consumption expenditure between the years 2002, 2005 and 2008 are discussed and depending on these factors, dimension of poverty is tried to be displayed. In the paper, pooled data set including a five year period using The Household Budget Surveys of these years .In the thesis, significant factors which determine the living standard according to the household consumption expenditure are discussed and depending on these factors, dimension of poverty is tried to be displayed. In applying the models pooled data set including three years using The Household Budget Surveys of the years are used. We compared the logit model ,nonparametrik logit model and semiparametric logit models for analysing the probability of hausehold poverty. The model performance is determined with performance criteria and deviance graphs.
Keywords: Ekonometri; Semiparametrik Logit Model; Yoksulluk